2022
DOI: 10.3389/fsoil.2022.835849
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture by Irrigation Modifies Microbial Communities and Soil Functions Associated With Enhancing C Uptake of a Steppe Semi-Arid Soil in Northern Patagonia

Abstract: The transformation of the semiarid steppe soil after 5 years of intensive irrigated agriculture in Northern Patagonia was analyzed in an on-farm study. The private grower venture used conservative practices, including no-till to maintain soil structure, high crop rotation and cover crops. To characterize steppe soil changes by irrigated agriculture, we analyzed the enzymatic activities involved in the biogeochemical cycles (carbon, nitrogen, phosphorus and sulfur), the whole soil fatty acids profile, the state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
2
1
0
Order By: Relevance
“…Conversely, irrigated plots had higher microbial diversity compared to the controlled plots. This trend supports previous studies from the same site (Colombo et al, 2016; Zheng et al, 2017) and from other regions (Frene et al, 2022; Hartman et al, 2018). Interestingly, the clusters from PCoA analysis and ANOVA results on the Shannon diversity index suggested that across all below‐ground microbiomes, irrigation alone and irrigation–fertilizer treatments had similar profiles, suggesting a stronger impact of irrigation on microbial community compared to fertilization treatments (Li et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, irrigated plots had higher microbial diversity compared to the controlled plots. This trend supports previous studies from the same site (Colombo et al, 2016; Zheng et al, 2017) and from other regions (Frene et al, 2022; Hartman et al, 2018). Interestingly, the clusters from PCoA analysis and ANOVA results on the Shannon diversity index suggested that across all below‐ground microbiomes, irrigation alone and irrigation–fertilizer treatments had similar profiles, suggesting a stronger impact of irrigation on microbial community compared to fertilization treatments (Li et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Based on MALDI-TOF MS and sequencing results, larval sources in irrigated areas had higher bacterial species diversity and abundance than sources in non-irrigated areas. Similar to previous research that linked increased soil bacterial abundance and diversity to irrigation [53,54], the findings of this study confirm the influence of irrigation on increased bacterial abundance and species diversity that may influence larval productivity on larval sources or pools. MALDI-TOF MS, revealed Shigella and Escherichia as the dominant genera in larval sources with larvae presence in irrigated areas.…”
Section: Plos Onesupporting
confidence: 89%
“…Conversely, irrigated plots had higher microbial diversity compared to the controlled plots. This trend supports previous studies from the same site (Colombo et al , 2015; Zheng et al ., 2017) and from other regions (Hartmann et al ., 2017; Frene et al ., 2022). Interestingly, the clusters from PCoA analysis and ANOVA results on the Shannon diversity index suggested that across all below-ground microbiome, irrigation alone and irrigation-fertilizer treatments had similar profiles suggesting stronger impact of irrigation on microbial community compared to fertilization treatments.…”
Section: Discussionmentioning
confidence: 99%